2022
DOI: 10.15240/tul/001/2022-2-003
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Employees’ Digital Skills in the Context of Banking 4.0

Abstract: Digitalisation and technical development in the financial service sector have aimed to secure, increase the quality, and satisfy the interests of both customers and financial institutions in the current turbulent era. Together with this situation, there is a need to develop digital employees’ competencies in the financial sector. This paper aims to analyse the topical issue of digitalisation and demand for employees’ digital skills in connection with the COVID-19 pandemic situation based on global secondary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The descriptive statistics data are in line with current trends in the banking scenario, reflecting the growing willingness of consumers to adopt digital channels, as observed in the works of [9,34]. The high average in the question about replacing face-to-face services (4.3) suggests an acceptance of this transition, in line with the growing digitalization in several sectors.…”
Section: Profile Studiedsupporting
confidence: 77%
See 2 more Smart Citations
“…The descriptive statistics data are in line with current trends in the banking scenario, reflecting the growing willingness of consumers to adopt digital channels, as observed in the works of [9,34]. The high average in the question about replacing face-to-face services (4.3) suggests an acceptance of this transition, in line with the growing digitalization in several sectors.…”
Section: Profile Studiedsupporting
confidence: 77%
“…The first two factors are related to economic aspects and the last to environmental aspects. It is suggested that the points with greater agreement are precisely those to which the customer is already feeling the benefits, with the reduction in service time and the increased satisfaction and practicality in subscribing to financial services, which is in line with the main findings of studies by [9,32,34]. Furthermore, the use of digitalization in the banking segment makes a noticeable reduction in waste and unnecessary inputs for current demands.…”
Section: Perception Of Sustainability 40supporting
confidence: 56%
See 1 more Smart Citation
“…Despite that digitalisation in construction may have been accelerated due to the pandemic (Mazurchenko and Zelenka, 2022) (Mazurchenko et al, 2020), drive financial incentives (Ninan et al, 2022), and prioritise feedback (Shojaei et al, 2022). However, the organisational influence on the adoption of innovation remains a complex interaction, and the understanding of it is limited across the construction context (Lin and Yi, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is decentralized because it is not governed by any authority or agency [56]. It is regarded as a "trust-building machine" [57]. The blockchain assists banks in implementing optimal information-processing mechanisms [58].…”
Section: New Technologiesmentioning
confidence: 99%